2020
DOI: 10.1002/slct.201904667
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Rapid Preparation of Vermiculite‐Loaded Nano‐Nickel Oxide As a Highly Efficient Catalyst for Acetylene Carbonylation to Synthesize Acrylic Acid

Abstract: With CuBr2 as a co‐catalyst, the nickel‐supported two‐dimensional layered vermiculite (2D‐VT)‐based composite [Ni(NO3)2•6H2O/2D‐VT] was used as a precursor and applied to various calcination methods to produce catalysts. These catalysts were used in the acetylene carbonylation reaction to synthesize acrylic acid (AA). The catalysts were characterized and evaluated by scanning electron microscope (SEM), transmission electron microscope (TEM), X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…There is also report on preparation of TiO 2 /G from GrpO, titanium isopropoxide, TTIP (variable) in isopropyl alcohol and N 2 H 4 via MW irradiation in a closed pyrex glass bottle. 161 The obtained dried precipitate was finally calcined at 400 °C for 4 h. 164 The overall size distribution and crystallinity again confirmed that MW method is superior for producing smaller grained highly crystalline NiO.…”
Section: Carbon Supportedmentioning
confidence: 80%
See 4 more Smart Citations
“…There is also report on preparation of TiO 2 /G from GrpO, titanium isopropoxide, TTIP (variable) in isopropyl alcohol and N 2 H 4 via MW irradiation in a closed pyrex glass bottle. 161 The obtained dried precipitate was finally calcined at 400 °C for 4 h. 164 The overall size distribution and crystallinity again confirmed that MW method is superior for producing smaller grained highly crystalline NiO.…”
Section: Carbon Supportedmentioning
confidence: 80%
“…206 MW-NiO/2D-Vmt catalyst performed better activity than the MF-NiO/2D-Vmt catalyst for acetylene carbonylation in a constant volume sealed container for synthesizing acrylic acid (AA). 164 Again, smaller NiO grains in the MW-NiO/2D-Vmt catalyst produced higher yield of AA (86 %), whereas, the MF-NiO/2D-Vmt catalyst produced 68 % yield. However, the MW-NiO/2D-Vmt catalyst was unstable, demonstrated drastic change in morphology and disappearance of NiO siganl after the first cycle.…”
Section: Oxidation Reactionsmentioning
confidence: 90%
See 3 more Smart Citations